(untitled) (Research, Society and Development, 2024)
Mental and behavioral disorders not only cause psychosomatic harm but also result in significant financial costs to public health expenditures, especially in hospital care. In light of this scenario, the present study aims to identify the epidemiological profile of patients hospitalized due to mental and behavioral disorders in the Southern region of Brazil between 2018 and 2023, in order to analyze the effectiveness of mental health care in the studied location and period. This is a retrospective, cross-sectional, and descriptive study using data obtained from public health surveillance and recorded in the Hospital Information System of SUS. The Southern region recorded 430,661 hospitalizations, with lower incidence in 2020 and variable peaks in the post-pandemic period. Paraná, although not having the highest incidence, had the highest mortality rate, length of stay, and hospitalization costs. The analysis indicates a prevalence of adult men and a high occurrence of emergency care, suggesting shortcomings in primary mental health care.